An exploration of Indonesian nurses' perceptions of barriers to paediatric pain management. (September 2017) - Mediani, Henny Suzana; Duggan, Ravani; Chapman, Rose; Hutton, Alison; Shields, Linda
There is a dearth of research in Indonesia regarding pain management in children. Previous studies have identified that although a variety of research and clinical studies on all aspects of pain have been conducted in many countries, children continue to experience moderate to severe pain during hospitalization. Greater research efforts are needed to identify and explore the factors that impede effective pain management in children. To address this gap, the researchers conducted an exploratory descriptive qualitative study to capture Indonesian nurses' perceptions of barriers to paediatric pain management in two hospitals. Using purposive sampling, data were collected from 37 nurses through semi-structured, in-depth interviews. Findings indicated that nurses working in Indonesian paediatric wards felt that they were not able to provide effective pain care to hospitalized children. Nurses identified several organizational structural and cultural factors that were thought to hinder their provision of effective pain care to paediatric patients. These factors are embedded in nurses' clinical practice. The study findings can assist to inform relevant initiatives and strategies to improve clinical nurses' performance and competency in providing effective pain care to paediatric patients.